Hallucinations in the child and adolescent "ultra-high risk" population: A systematic review. Issue 1 (4th November 2022) - Di Luzio, Michelangelo; Pontillo, Maria; Di Vincenzo, Cristina; Bellantoni, Domenica; Demaria, Francesco; Vicari, Stefano
Abstract: Background and Hypothesis: Ultra-high risk for psychosis young adults are assumed to be at higher risk of developing a psychotic spectrum disorder. Predominantly, the ultra-high risk population is aged 18–35 years, but it may also include younger children and adolescents. Individuals in this population experience psychosis prodromes in the form of attenuated or brief psychotic symptoms (particularly perceptual abnormalities). Albeit diagnosis is made via structured interviews, such measures fail to sufficiently assess the precise form and content of perceptual abnormalities, especially as they manifest in children and adolescents. Study Design: The present study involved a systematic review of the literature on perceptual abnormalities (particularly hallucinations) in ultra-high risk children and adolescents. Study Results: The analysis reviewed five studies and drew conclusions about the perceptual abnormalities (i.e., hallucinations) experienced by the study samples, focusing on form, content, and associations with other symptoms. Of note, two of the investigated studies suggested a relationship between hallucinations and experiences of childhood trauma. Conclusions: The transition to psychosis and experiences of childhood trauma could correspond to different types of hallucinations in ultra-high risk children and adolescents. This knowledge could improve the identification of prodromal states in the young, ultra-high risk population.